THE FORENSICS EXHIBITION: Displaying Human Remains as Material Evidence of Genocide. (2nd September 2022) - Gill, Fiona
Abstract : This paper examines the role of human remains in genocide memorials and museums to evoke and narrate individual experiences of genocide. Understanding that the display of human remains is contested, I suggest that their presence in memorials and museums can play a valuable, but hitherto neglected, role in the development of individualized and evidentiary narratives of genocide. Such narratives, developed through explicit information regarding the provenance of the remains and the forensic analysis conducted, can deepen the engagement with and understanding of the victims of genocide by museum visitors. Based on the Forensics Exhibition in Tuol Sleng, Cambodia, I argue that explicitly displaying and explicating the remains develops a powerful evidentiary narrative complementing those developed in more familiar exhibitions. In so doing, I expand on debates regarding the liminal position of human remains as person and object, arguing that the display of such remains in a forensic and public context supports engagement with the remains as individuals. In so doing, the paper provides an opportunity to consider the management of the dead and human remains in the aftermath of mass violence and genocide, attempting to marry the emotional and social needs of the survivors with the desire for "evidence" articulated in the legal, historical, and pedagogical realms.